Methodological Peculiarities of the Foundation of Gnoseology - Skersytė, Jūratė (Problemos, 1987)
Historical-theoretical preconditions of the problem of gnoseological fundamentals are considered. The methodological contents of the problem is explicated on the basis of Descartes’ philosophy. It is claimed that Descartes adequately specified the methodological peculiarities of the problem stating it as a problem of structurally undefinable criteria of the true thinking of being and by solving it via the explication of the genesis of such thinking.